2020
DOI: 10.1155/2020/5285362
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical Characteristics and Brain Activity between Patients with Low- and High-Frequency Tinnitus

Abstract: This study was aimed at delineating and comparing differences in clinical characteristics and brain activity between patients with low- and high-frequency tinnitus (LFT and HFT, respectively) using high-density electroencephalography (EEG). This study enrolled 3217 patients with subjective tinnitus who were divided into LFT (frequency<4000 Hz) and HFT (≥4000 Hz) groups. Data regarding medical history, Tinnitus Handicap Inventory, tinnitus matching, and hearing threshold were collected from all patients. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…The EEG data preprocessing analysis was performed as described in our previous study [ 38, 39 ]. The EEG data pre-processing analysis was conduct by EEGLAB toolbox and scripts written in MATLAB2014a (The Mathworks, Natick, MA) as described in our previous study.…”
Section: Methodsmentioning
confidence: 99%
“…The EEG data preprocessing analysis was performed as described in our previous study [ 38, 39 ]. The EEG data pre-processing analysis was conduct by EEGLAB toolbox and scripts written in MATLAB2014a (The Mathworks, Natick, MA) as described in our previous study.…”
Section: Methodsmentioning
confidence: 99%
“…A PET study also confirmed the increased angular gyrus activity in patients with chronic tinnitus (Song et al, 2012). This may be related to the function of the angular gyrus to participate in the integration of auditory stimuli, memory-related activities, self-awareness, and self-perception (Daselaar et al, 2006;De Ridder et al, 2014;Zhang et al, 2020). Moreover, the angular gyrus is involved in shifting the attention of chronic tinnitus patients from auditory phantom percept to visual cues in Heidelberg neuro-music therapy (Krick et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, in the present study, increased CBF and normal ReHo were found in the right angular gyrus, suggesting that the increase in the CBF/ReHo ratio was mainly caused by increases in CBF. Prior studies showed that in patients with unilateral tinnitus, synchronized activity and connectivity within the gamma band were increased in the right angular gyrus as assessed using electroencephalography (Vanneste et al, 2011;Zhang et al, 2020). Chen et al (2014) based on fMRI, found increased low-frequency fluctuations in chronic tinnitus patients, indicating increased neuronal activity in this region (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…It is known from the literature that low-frequency tinnitus (LFT) is perceived and processed differently from high-frequency tinnitus (HFT) ( Zhang et al, 2020 ). However, in the tinnitus participants recruited in this study, we did not deliberately distinguish between patients with LFT or HFT.…”
Section: Methodsmentioning
confidence: 99%